When your teen has an eating disorder : practical strategies to help your teen recover from anorexia, bulimia & binge eating - Muhlheim, Lauren (New Harbinger Publications, Inc., 2018)
Having a teen with an eating disorder can leave parents feeling helpless. To help empower these parents, a clinical psychologist and expert in eating disorders offers an evidence-based program using family-based treatment (FBT) to help parents and caregivers take charge of their teen's nutritional rehabilitation, which includes normalizing eating behaviors, managing meals, expanding food flexibility, teaching independent and intuitive eating habits, and utilizing coping strategies and recovery skills to prevent relapse.